Malay speech recognition in normal and noise condition - Fook, C. Y.; Hariharan, Muthusamy, Dr.; Sazali, Yaacob, Prof. Dr.; Abdul Hamid, Adom, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/